Konsep Halal Dalam Produksi Makanan Di Indonesia - Amelia, Rizqa; Nasution, Muhammad Iqbal; Fachrezi, Harahap Adrie (Jurnal Manajemen Akuntansi (JUMSI), 2023)
In Islam, Halal Food is an obligation that must be carried out because it relates to the commands of Allah SWT. This study aims to find out how the Halal concept is applied in food production in a business in Indonesia. This study uses a qualitative method, because problems related to humans are basically observational in nature. Bogdan and Taylor define qualitative methodology as a research process that produces descriptive data in the form of text or speech of people and observed behavior. This research method uses a descriptive method (Lexy Moleong, 2009). Descriptive method is a research method that seeks to describe and explain objects according to their nature. Descriptive research is usually done with the main objective. In this research, the writer wants to know what the concept of Halal is that is applied in food production in a business in Indonesia. The results of the discussion in this study are that Muslims must understand the idea of halal and haram in consumption to make ethical decisions about the food and drinks they choose to consume. consumed. Considering that the majority of Indonesia's population are Muslims who adhere to Islamic law, halal food is very important in the country. Overall, Halal cuisine is very important in Indonesia as it promotes cleanliness, health and complies with Islamic teachings, which are practiced by the majority of the country's citizens. Halal awareness is very important for everyday life, especially for Muslims. Halal is a term used to describe food, drink and other goods that comply with Islamic law.